2001
DOI: 10.1016/s1350-4177(01)00083-9
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical degradation for toxic halogenated organic compounds

Abstract: This paper describes the degradation of p-chlorophenol using three different ultrasonic devices. The dissipated power in the reaction matrix was measured based on calorimetric method. The study showed that hydrogen peroxide can improve the sonochemical reaction and gases dissolved in reaction matrix can affect the process to a small extent. The reaction mechanism and kinetics of degradation were also investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(24 citation statements)
references
References 5 publications
1
23
0
Order By: Relevance
“…Over the last decade there has been an increased interest in ultrasound to degrade chlorinated phenolic contaminants present in water and/or wastewater (Bapat et al 2008;Chowdhury and Viraraghavan 2009;Isariebel et al 2009;Katsumata et al 2007;Nakui et al 2009;Rehorek et al 2007;Svitelska et al 2004;Vassilakis et al 2004). Compared with other treatment technologies such as UV light, high voltage corona, incineration, and solvent extraction, it is known that sonochemical degradation has significant advantages such as safety, cleanliness, and energy conservation without causing secondary pollution (Hao et al 2003;Teo et al 2001). In general, the sonochemical degradation of pollutants in an aqueous phase occurs as a result of imploding cavitation bubbles and involves representatively two reaction pathways such as pyrolysis inside the bubble and/or at the bubble-liquid interface and hydroxyl radical induced reactions at the bubble-liquid interface and/or in the liquid bulk (Adewuyi 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade there has been an increased interest in ultrasound to degrade chlorinated phenolic contaminants present in water and/or wastewater (Bapat et al 2008;Chowdhury and Viraraghavan 2009;Isariebel et al 2009;Katsumata et al 2007;Nakui et al 2009;Rehorek et al 2007;Svitelska et al 2004;Vassilakis et al 2004). Compared with other treatment technologies such as UV light, high voltage corona, incineration, and solvent extraction, it is known that sonochemical degradation has significant advantages such as safety, cleanliness, and energy conservation without causing secondary pollution (Hao et al 2003;Teo et al 2001). In general, the sonochemical degradation of pollutants in an aqueous phase occurs as a result of imploding cavitation bubbles and involves representatively two reaction pathways such as pyrolysis inside the bubble and/or at the bubble-liquid interface and hydroxyl radical induced reactions at the bubble-liquid interface and/or in the liquid bulk (Adewuyi 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Teo et al [40] reported that the increase in concentration of H 2 O 2 increased the initial rate of degradation of 0.4 mM of p-chlorophenol with an increase in H 2 O 2 concentration from 0 to 20 mM but further increase in H 2 O 2 concentration to 40 mM showed a marginal effect on degradation. Furthermore, the increase in concentration beyond 40 mM decreased the rate of degradation.…”
Section: Effect H 2 O 2 Dosagementioning
confidence: 99%
“…Teo et al 25 studied the effect of hydrogen peroxide on the degradation of 4-CP. It was observed that initially the decomposition rate of 4-CP increased with the concentration of hydrogen peroxide, reaching a maximum at C H 2 O 2 = 30 mM, approximately.…”
Section: Cah Degradation Promoted By Ultrasonic Irradiation Alonementioning
confidence: 99%